Persepsi Siswa Kelas XI Terhadap Layanan Bimbingan Klasikal Di SMAN 7 Semarang - Meynar, Shalima; Kurniawan, Kusnarto (Indonesian Journal of Guidance and Counseling: Theory and Application, 2013)
The research was conducted based on the results of interviews with 23 students of class XI in SMAN 7 Semarang on 9 February 2015. The study was conducted in class XI SMAN 7 Semarang, the subject of 90 students. Class XI student population SMAN 7 Semarang totaling 356 students. The data collection method used was survey method. The purpose of this study was to determine the perception of class XI student of classical guidance services at SMAN 7 Semarang. The method used is the method of survey research. The analysis technique used is descriptive analysis techniques percentage. The overall results of this study are 90 students of class XI contained 10% or 9 students who have a very positive perception of classical guidance services. 47 students or 52.2% have a positive perception of classical guidance services. Furthermore, 33.3% or 30 students perceive classical guidance services with quite positive and 4 students or 4.4% have a negative perception of classical guidance services. The criteria are very positive not have a percentage of 0%. It can be concluded that 52.2% or 47 class XI student at SMAN 7 Semarang has a relatively positive perception of classical guidance services.